KAIDAH QIRA’AT IMAM NAFI’ RIWAYAT WARSY DAN PENERAPANNYA Di Pondok Pesantren Tahfizhul Qur’an Putri Al-Lathifiyyah Palembang - Lailatul Mu’jizat (Al-Dirayah, 2020)
: This research is motivated by the emergence of Qira'at knowledge which must be studied and practiced so that it is not lost and considered foreign by Muslims. This type of research is a field research (field research). While the type of data used is qualitative data. Sources of data used in this study are primary data sources and secondary data sources. In analyzing data using three procedures, namely data reduction, data presentation, and data verification or drawing conclusions. Qira'at is a science that studies the different ways of pronouncing al- Qur'an which is adopted by one of the Imams based on the sanad-sanad which is continued to the Prophet Muhammad. In order to carry out the teachings of the Prophet, the leadership of the Al-Lathifiyyah Islamic Boarding School for the daughter of Al-Lathifiyyah in Palembang carried out the agenda of grounding the Qira'at, in this case the Qira'at Imam Nafi 'History of Warsy. There are several things that become the reference for this research, namely: What is the rule of Qira'at Imam Nafi from Warsy?, how are the efforts to implement the Qira'at Imam Nafi History of Warsy at Pondok Pesantren Tahfizhul Qur'an Putri Al-Lathifiyyah Palembang? And what are the problems experienced by students in understanding Qira'at Imam Nafi, according to Warsy in the Islamic boarding school Tahfizhul Qur'an Putri Al-Lathifiyyah Palembang ?. The results of this study concluded that the rules of Qira'at Imam Nafi from Warsy's history were to use the ushuliyyah rule and the Farsyul letter rule. Meanwhile, the application of the learning process of Qira'at Nafi 'in Warsy's history is to use a variety of reading Bi al-ifrad (Mufrod Method), namely Qori' reading qira'at by specifying the variety of readings from one narration. The history used is Imam Nafi's history 'Warsy's history. Talaqqi and sima'i systems and with a Tadwir tempo. The problems experienced by Santriwati in Qira'at learning at the Tahfidzul Qur'an Putri Al-Lathifiyyah Islamic Boarding School in Palembang include: shortness of breath, due to age, lack of interest in learning Qira'at, laziness, difficulties in the rules and limited time in learning Qira'at